ASUPAN VITAMIN A, STATUS VITAMIN A, DAN STATUS GIZI ANAK SEKOLAH DASAR DI KECAMATAN LEUWILIANG, KABUPATEN BOGOR - Marliyati, Sri Anna; Nugraha, Aji; Anwar, Faisal (Jurnal Gizi dan Pangan, 2014)
The objective of this research was to study the intake of vitamin A, vitamin A status, nutritional status and health status of primary school children in Leuwiliang Sub—District, Bogor Regency. There were 31 children grade 2 and 3 in SD Angsana I and II Cibeber Village selected by purposive sampling technique. The results showed that more than half of the children had medium sufficient levels of vitamin A (54.8%). Generally, they had normal nutritional status (93.5%). More than half of children had low vitamin A status. The result also found that relationship between the level of adequacy of energy and protein with nutritional status of the children were not significant (p>0.05). The relationship between intake of vitamin A to vitamin A status also showed no significant relationship (p>0.05). It was presumably due to the presence of other factors (food consumption, reserves of vitamin A in the liver, and socio-economic). There was no significant relationship between nutritional status and vitamin A status (p>0.05).